Promosi Keselamatan dan Kesehatan Kerja dengan Media Video terhadap Peningkatan Pengetahuan dan Sikap Pekerja Sektor Informal di Kota Pontianak - Katriana, Katriana; Suwarni, Linda; Selviana, Selviana (Universitas Muhammadiyah Semarang, 2024)
Background: Occupational Health and Safety (K3) risks are higher in the informal sector, including MSMEs. The lack of access to K3 promotion causes the knowledge and attitudes of workers in the informal sector to be inadequate. The aim of this research is to determine the effectiveness of K3 promotion using video media in increasing the knowledge and attitudes of informal sector workers in Pontianak City. Methods: his research is a pre-experimental research with a one group pretest-posttest design approach. The population in this study were all MSMEs in Pontianak City, with a total sample of 31 people (purposive sampling). The time of research implementation was in August 2024. Data were analyzed univariately and bivariately (paired t test with a confidence level of 95%). Results: The average knowledge score before the K3 promotion using video was 7.19, and after it was 9.03 (delta mean knowledge was 1.84). The average attitude score before the K3 promotion using video was 30.32, and after it was 33.19 (delta mean attitude score was 2.87). The results of the paired t test show that there is a significant difference between K3 promotion using video media on increasing knowledge and attitudes (p value < 0.05). Conclusion: Video media on the application of K3 in the home industry is effectively used to increase the knowledge and attitudes of informal sector workers. It is necessary to develop other similar educational video media in the form of video demonstrations, especially regarding ergonomic working positions, and efforts to prevent and improve occupational health and safety.